The Ecophysiological Role of Trees in Dryland Agroecosystems: Implications for Natural Resource Conservation and Sustainable Food Production in Sub-Saharan Africa - Priyadarshini, K. V. R.; Prins, Herbert H. T.; de Bie, Steven (Diversity (Basel), 2025)
Agroforestry involves maintaining trees alongside crops and is widely recognised to provide multiple benefits, including improving food security, production efficiency, and soil quality and mitigating climate change. However, in Sub-Saharan Africa, a predominantly dry landscape, various pressures are leading to the removal of trees from farmlands. Evidence from natural dryland systems shows that trees play a central role in regulating the key ecological processes of nutrient and water redistribution, an aspect also invoked in dryland agroecology. In this paper, we synthesise the ecophysiological functioning of trees, focusing on two key processes: water and nutrient redistribution. Additionally, we synthesise the influence of these functions on soil biotic interactions, detailing their ecological significance. Based on available evidence from both natural and agroecosystems, we review the role of tree ecophysiology in sustainable food production in dryland agroecosystems of Sub-Saharan Africa. We provide caveats related to prevalent interpretations and the current understanding of plant resource use in agroecology. Trees in agroforestry systems of Sub-Saharan Africa play a potentially critical role in the ecological intensification of food production. However, there is a lack of data on the roles of tree functions in enhancing crop yields and conserving resources in this region. Although evidence from natural drylands and indirect evidence from dryland agroforests indicate that tree ecophysiological functions may be crucial for ecological intensification of food production in Sub-Saharan Africa, many claims related to agroecosystems are overstated, underscoring the urgent need for focused research. Importantly, large trees on farms need to be conserved. To effectively exploit ecosystem services provided by trees, a key feature of ecological intensification, research tailored to local farm conditions is needed, with a focus on maintaining soil quality, securing long-term productivity, and conserving resources. Balancing agricultural intensification with ecological sustainability remains a challenge, yet it is vital for addressing food security, land degradation, and climate change.